APLICATION OF MARKETING COMMUNICATION SALES MARKETING DIVISION AT PT. SELA EXPRESS TOUR PEKANBARU - Yandi, Okta Dwi; Sidiq, Siti Sofro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Marketing communication is an activity that helps guests in making decisions and of course there is a process of influencing the choice of prospective buyers. Therefore travel agents must have marketers who are capable of communicating with guests, so guests will be influenced to buy packages from companies, especially sales marketing. This study aims to determine guest responses about the application marketing communication of sales marketing divisions at PT. Sela Express Tour Pekanbaru. To find out the response of guests about marketing communication as measured by 5 components, that : for the audience, consider time and cost, more than one purpose, well-organized, pay attention to the tone and influence on the audience. research will be known and measured by quantitative descriptive methods. This study sampled 80 respondents taken using the theory from Singarimbun. Data collection techniques in this study used observation, questionnaires, documentation and interviews. To measure the data interval in this study using a Likert scale. Based on the results of the study showed that guest responses to the application of marketing communication sales marketing division at PT. Sela Express Tour Pekanbaru is included in the excellent category. Keywords : customers response, marketing communication, sales marketing, travel agents